The Position of Non-Muslims in the Implementation of Islamic Law in Aceh, Indonesia - Mursyid Djawas; Andi Sugirman; Bukhari Ali; Muqni Affan; Idham Idham (AHKAM : Jurnal Ilmu Syariah, 2023)
The position of non-Muslims living alongside Muslims is evident in the history of Islamic law. Since the time of the Prophet, Companions and governments after non-Muslims lived peacefully and were protected. However, when Muslim countries formed nation-states, several problems arose, including their position as citizens, including in Indonesia, especially in Aceh, which formally applied Islamic law. This study is an empirical legal study that examines the implementation of Islamic law in society by using legal and political theory. The data used is a literature study examining several Sharia courts' decisions in Aceh; Banda Aceh, Sabang, Meulaboh, Kutacane, Takengon, and Singkil. This study concludes that non-Muslims chose to concentrate after implementing the Islamic shari'a qanun. According to them, Qanun Jinayat is more efficient, affordable, effective, and quick in resolving problems. It has been proven in several cases, such as maysir, khalwat (ikhtilāṭ), khamr, and sexual harassment. Therefore, in legal politics, Islamic sharia and Qanun Jinayat, born from a democratic legal configuration, give birth to laws that are fair and equal and do not discriminate against non- Muslims. In several cases above, non-Muslims voluntarily chose to devote themselves to Islamic law.  Abstrak: Kedudukan non-Muslim yang hidup berdampingan dengan umat Islam sejatinya sudah jelas dalam sejarah hukum Islam. Sejak masa Nabi, Sahabat dan pemerintahan sesudah non muslim hidup secara damai dan dilindungi. Namun demikian ketika negera-negara Muslim membentuk sebagai negara bangsa timbul beberapa persoalan, diantaranya kedudukannya sebagai warga negara, termasuk di Indonesia, apalagi di Aceh yang menerapkan hukum Islam secara formal. Kajian ini merupakan studi hukum empiris yakni menelaah implementasi hukum Islam dalam masyarakat dengan menggunakan teori politik hukum. Data yang digunakan adalah studi literature dan menelaah beberapa putusan mahkamah syariat di Aceh; Banda Aceh, Sabang, Meulaboh, Kutacane, Takengon dan Singkil. Penelitian ini menyimpulkan bahwa pasca penerapan qanun syariat Islam, non muslim justru memilih untuk me- nundukkan diri. Menurut mereka, Qanun Jinayat lebih efisien, terjangkau, efektif, dan cepat dalam menyelesaikan masalah. Terbukti dalam beberapa kasus seperti maisir, khalwat (ikhtilāṭ), khamar, dan pelecehan seksual. Karena itu, dalam konteks politik hukum, syariat Islam dan qanun jinayat yang lahir dari konfigurasi hukum yang demokratis melahirkan hukum yang adil dan setara tidak diskriminatif termasuk kepada non-Muslim. Non-muslim pada sejumlah kasus di atas, memilih untuk menundukkan diri kepada syariat Islam secara sukarela.